Jumping phenomena and prediction of jumping torque in timing belt drives - Kiyoshi OKURA; Susumu OSAKI; Takumi MIZUMOTO; Shuhei NISHIDA; Yuji MARUYAMA (Nihon Kikai Gakkai ronbunshu, 2021)
In order to prevent timing belt jumping, which often occurs under high loads, a practical jumping torque prediction formula was studied and the following results were obtained. (1) Jumping occurs when the amount of belt elongation on the tight side span due to the increase in load after the slack side tension becomes zero is equal to the amount of belt elongation due to the belt lifting on the pulley when the lifting reaches the belt tooth height in the whole wrapping area. A jumping torque prediction formula was derived based on this mechanism. The prediction formula includes parameters such as pulley diameter, span length, wrapping angle, belt tooth height, belt extensional rigidity, initial tension, and belt speed. (2) To compensate for the difference between the basic theory of frictional transmission applied in the prediction formula and the actual phenomenon, four correction factors were introduced for the amount of belt elongation caused by the belt lifting, etc., and physical properties of belt teeth. This makes it possible to predict the jumping torque of not only the driven pulley but also the driving pulley, and to expand the application range and improve the prediction accuracy. (3) The four correction factors were obtained by running tests using curvilinear profile S8M type belt, but it was shown that they are also applicable to a trapezoidal profile L type belt. (4) Jumping tests at rest with the driven pulley shaft fixed were conducted, and it was confirmed that the jumping torque of the driving pulley at running was about twice that of the driven pulley, and almost equal to that of the driving and driven pulleys at rest.